WORKSHOP PENULISAN BERITA JURNALISTIK: MENINGKATKAN KETERAMPILAN MASYARAKAT KABUPATEN LOMBOK UTARA DALAM MENGHADAPI ERA DIGITAL DAN MISINFORMASI: Journalistic News Writing Workshop: Improving The Skills Of North Lombok District Communities In Dealing With The Digital Era And Misinformation - Putra, Sandi Justitia; Audina, Pin Kharisma; Mandini, Denda Devi Sarah; Husbuyanti, Irma El-Mira; Ningrum, Anisa Purwa; Rahmat, Lalu Ahmad; Rahmandari, Ismi Arifiana; Sumanjayadi, Sumanjayadi; Hambali, M. Saleh; Arisandy, Rita; Sarlan, Yani Rosita; Zulhadi, Zulhadi (Al-Amal: Jurnal Pengabdian Masyarakat, 2024)
Journalistic News Writing Workshop with the theme "Producing Creative and Innovative Contemporary Citizen Journalism" in Bentek Village, North Lombok. This activity was designed using a participatory method, involving material presentation, group discussions, simulations, and direct practice. The training materials covered basic journalistic concepts, news writing techniques, journalistic ethics, and the use of digital media. The evaluation results showed a significant increase in participants' understanding of journalistic literacy, news writing skills, and awareness of the importance of ethics and information verification. As many as 90% of participants succeeded in publishing news through digital platforms by utilizing creative content presentation strategies. This activity makes a real contribution to supporting a healthy and responsible information ecosystem, while strengthening local community participation in the process of delivering quality news. Through instilling journalistic literacy, it is hoped that a citizen journalism community will be formed that has integrity and has a positive impact on society